(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The main document containing training requirements for students and recommendations for their teaching of foreign languages is the Qualification requirements for the Bachelor’s degree program in Foreign Language and Literature-60111800: English Language, approved by the order №344 of August 8, 2023-year of the Ministry of Higher Education, Science, and Innovation of the Republic of Uzbekistan. This Qualification requirements for the Bachelor’s degree program in Foreign Language and Literature-60111800 includes the following sections: